2022
DOI: 10.1021/acs.estlett.2c00627
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Offloading of Per- and Polyfluoroalkyl Substances to Eggs by Lake Michigan Salmonids

Abstract: Per- and polyfluoroalkyl substances (PFAS) distribute and bioaccumulate within aquatic organisms and food webs. Many PFAS are proteinophilic compounds that display higher concentrations in the blood, liver, and kidney of vertebrates than in muscle. Several studies have shown that birds and mammals exhibit maternal offloading of PFAS to offspring through transport to the placenta, milk, and egg deposition, but no study to date has observed maternal offloading in fish. We analyzed PFAS concentrations in muscle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the US, Robuck et al [ 75 ] confirmed the presence of PFAS in various tissues and organs of juvenile seabirds. According to various research studies, there is evidence of increased concentrations of PFAS in polar bears, seabirds, fish, and other environmental receptors, posing a health risk to developing animals, globally, as well as a contamination risk to the food chain [ [76] , [77] , [78] ]. For environmental matrices, a comprehensive review was conducted on PFAS in global surface water that revealed high levels of PFOS and PFOA, exceeding US EPA advisory limits, and identified direct discharge and atmospheric deposition as key sources [ 79 ].…”
Section: Environmental Occurrence and Ecotoxicological Effects Of Pfasmentioning
confidence: 99%
“…In the US, Robuck et al [ 75 ] confirmed the presence of PFAS in various tissues and organs of juvenile seabirds. According to various research studies, there is evidence of increased concentrations of PFAS in polar bears, seabirds, fish, and other environmental receptors, posing a health risk to developing animals, globally, as well as a contamination risk to the food chain [ [76] , [77] , [78] ]. For environmental matrices, a comprehensive review was conducted on PFAS in global surface water that revealed high levels of PFOS and PFOA, exceeding US EPA advisory limits, and identified direct discharge and atmospheric deposition as key sources [ 79 ].…”
Section: Environmental Occurrence and Ecotoxicological Effects Of Pfasmentioning
confidence: 99%